(Cambridge IGCSE) First language english. coursebook (fourth edition) - Cox, Marian (Cambridge University Press Cambridge, 2014)
Up-to-date resources providing full coverage of Cambridge IGCSE® First Language English (0500 and 0522) for first examination in 2015.